Surveillance, integrity and metadata in the information age - Peter Bennesved (Lychnos)
In August 1994, the Prime Minister of Sweden, Carl Bildt, publicly announced the formation of The Information and Communication Technology Commission. This was an advisory commission, comprised of ministers in Bildt’s government cabinet as well as invited experts and entrepreneurs.  The formation of the ICT Commission has been understood as a pivotal moment in Swedish policymaking within the ICT area. However, an underappreciated part of the ICT Commission’s history is that while it is generally acknowledged that the introduction of ICT in the 1990s was positively received by political elites and intellectuals, public scepticism toward ICT was a known problem and something the commission needed to address. Inspired by the concept of sociotechnical imaginaries (STIM), developed by STS scholars Jasanoff and Kim, the ICT Commission can be interpreted as a sort of state-financed “embedding activity” meant to overcome public scepticism of perceived risks, and to gather around a common vision of the future. Starting from a STIM perspective, the aim of this article is to deepen our understanding of this period in Swedish ICT policymaking, and its consequences. Studying the way the ICT Commission addressed topics of surveillance, personal integrity and metadata is important in that it provides a new and more complex perspective on the commission’s work and its public role. The article also connects the commission’s history to contemporary discussions about surveillance cultures and asks if the Commission – in a longer perspective – can be said to have fostered a positive attitude toward data sharing.